Regresi Data Panel Indeks Pembangunan Manusia Provinsi Kepulauan Bangka Belitung - Yulianto, Safa’at; Dwinda, Dede (UIN Walisongo Semarang, 2024)
The Human Development Index (HDI) isused as tool to measure the success or failure of program aimed at improving the quality of human life. Itserves as determinant of the level of development of a country or region.. in this research, panel data is utilized in the form of a combination of cross-section and time series. This type of data can provide insights into two types of information: inter-unit and inter-time information. Panel data regression is a regression with a data structure in the form of data on the diversity of location aspects alone but also influenced by other factors. The purpose of this study was to determine the factors that affect the quality of life in the Bangka Belitung Islands Province. As a result of this study, the best panel data regression model uses the Random Effect Model (REM). Life expectancy variables, average years of schooling, expected years of schooling and per capita expenditure were able to explain HDI in the Bangka Belitung Islands Province by 99.80%. The panel data regression equations are IPMit = 4.904 + 0,488 UHHit + 1,322 RLSit + 1,004 HLSit + 0,000 PPit.Keywords: HDI, Random Effect Model, Panel Data Regressioan.